Curriculum Management and Its Relevance to Workforce Demands: A Case Study at SMK Al-Barokah - Hilmi Sudarjat Barokah; Mohd Imraan (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
This study aims to analyze curriculum management and its relevance to workforce demands through a case study conducted at SMK Al-Barokah. A qualitative approach using a case study design was employed to obtain a deeper understanding of curriculum management practices within the context of vocational education. Research participants were selected through purposive and snowball sampling techniques, involving the school principal, vice principal for curriculum affairs, vocational teachers, heads of vocational programs, students, and Business and Industrial Sector (Dunia Usaha dan Dunia Industri/DUDI) partners. Data were collected through observations, in-depth interviews, and documentation studies. Subsequently, all data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing processes. The findings indicate that curriculum management at SMK Al-Barokah is implemented through stages of planning, implementation, evaluation, and curriculum adjustment directed toward workforce needs. The study identified three major factors influencing curriculum relevance, namely school–industry partnerships, teachers’ abilities to adapt instructional practices, and curriculum development flexibility. The school has integrated Industrial Work Practice (Praktik Kerja Lapangan/PKL), project-based learning, and work-oriented skill enhancement into instructional activities. However, industrial involvement in curriculum development remains largely consultative and has not yet fully contributed to strategic decision-making processes. Simultaneously, the rapid pace of industrial transformation frequently causes delays in curriculum adjustment processes. From a theoretical perspective, this study strengthens the social constructivist perspective by conceptualizing curriculum as a social practice that evolves through interactions among educational stakeholders. From a practical standpoint, the findings highlight the importance of strengthening school industry collaboration, enhancing teachers’ competencies, and developing more adaptive curriculum systems to improve the relevance of vocational education to workforce demands.